Evolutionary Constraints on the Norovirus Pandemic Variant GII.4_2006b over the Five-Year Persistence in Japan - Sato, Hironori; Yokoyama, Masaru; Nakamura, Hiromi; Oka, Tomoichiro; Katayama, Kazuhiko; Takeda, Naokazu; Noda, Mamoru; Tanaka, Tomoyuki; Motomura, Kazushi (Frontiers in Microbiology, 2017)
Norovirus GII.4 is a major cause of global outbreaks of viral gastroenteritis in humans, and has evolved by antigenic changes under the constantly changing human herd immunity. Major shift in the pandemic GII.4 strain periodically occurs concomitant with changes in the antigenic capsid protein VP1. However, how the newly emerged strain evolves after the onset of pandemic remains unclear. To address this issue, we examined molecular evolution of a pandemic lineage, termed the GII.4_2006b, by using the full-length viral genome and VP1 sequences (n=317) from stools collected at 20 sites in Japan between 2006 and 2011. Phylogenetic tree showed a radial diversification of the genome sequences of GII.4_2006b, suggesting a rapid genetic diversification of the GII.4_2006b population from a few ancestral variants. Impressively, amino acid sequences of the variable VP1 in given seasons remained as homogeneous as those of viral enzymes under annual increase in the nucleotide diversity in the VP1 coding region. The Hamming distances between the earliest and subsequent variants indicate strong constraints on amino acid changes even for the highly variable P2 subdomain. These results show the presence of evolutionary constraints on the VP1 protein and viral enzymes, and suggest that these proteins gain near maximal levels of fitness benefits in humans around the onset of the outbreaks. These findings have implications for our understanding of molecular evolution, mechanisms of the periodic shifts in the pandemic NoV GII.4 strains, and control of the NoV GII.4 pandemic strain.